FUNGSI PRINSIP ASAS KEBANGSAAN DALAM UNDANG -UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA - Darma Putra Sucahya, I Made; Eka Wisanjaya, I Gede Pasek (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013, 2013)
Nationality principle within Agrarian Act stipulated within Article 1, Article 9, Article 21 Section 1 and Article 26, Section 1 and 2, is functioned internally and externally. Its internal function is designed as the unifying factor of Indonesians whose economically unstable towards the stable ones. Meanwhile, is externally functioned to prevent land ownership by foreigners. Analysis towards the function of the principle is essentially needed in order to confirm the management of ownership so that it is also in line towards the goal of Agrarian Act. Thus, through this writing, several basic principles shall be explained. In addition, the function of nationality principle shall also be explained.
Keywords: Function, Nationality Principle, Agrarian Act